Pathogenic interaction between Escovopsis weberi and Leucoagaricus sp.: mechanisms involved and virulence levels - Marfetan, Jorge Ariel (2015)
Attini are the only ants that use fresh plant material to cultivate species of Leucoagaricus, which are their source of nutrition. Escovopsis species are specialized mycoparasites of Leucoagaricus sp. and Escovopsis parasitism has a negative impact on the health of the ants' colonies. The goals of this work were: to test if the virulence of different isolates of Escovopsis weberi were the same across Leucoagaricus sp. and to analyze if structural mechanisms were related to variation in the virulence of E. weberi isolates. All E. weberi isolates were able to parasitize isolates of Leucoagaricus spp. but with striking differences in virulence, and it was shown that the contact between hyphae of both fungi was the main process that generates the degradation of Leucoagaricus isolates. Additionally, the two most virulent isolates produced hook-like protuberances, increasing the damage caused to its target. Finally, E. weberi was re-classified as a destructive biotrophic parasite.